Targeting MLCK1 uncouples immune checkpoint inhibitor-induced colitis from antitumour immunity: intestinal inflammation - Xiong, Lei; Huang, Jianshang; Dong, Yunsheng; Han, Wei; Kuo, Wei-Ting; Xu, Wentao; Han, Yiran; An, Chenchen; Zhu, Rumeng; Zhu, Nina; Xia, Hanqi; Rahman, Abduxukur; et al. (Gut, 2026)
Objective Immune checkpoint inhibitors (ICIs) have revolutionised cancer treatment and patients’ survival. However, ICIs also cause severe immune-related adverse events, notably colitis, resulting in ICIs therapy discontinuation and tumour immunotherapy failure. This study investigates long myosin light chain kinase 1 (MLCK1), a known regulator of tight junction and gut permeability, to elucidate the mechanisms underlying ICI-mediated colitis and identify approaches to reduce this toxicity. - Design This study employed an integrated approach, using clinical samples, in vivo models and in vitro organoid systems. Biopsies from patients with ICIs colitis were profiled using single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics. To recapitulate human ICIs colitis, we used a wild mouse microbiota (WildR) model, alongside various genetically modified and tumour-bearing models (including melanoma and MC38). Furthermore, mechanisms were investigated through organoid-immune cell co-cultures. Finally, surface plasmon resonance, microscale thermophoresis, full-spectrum flow cytometry, bulk RNA sequencing, immunostaining, ELISA and gut permeability assays were performed to comprehensively delineate the underlying molecular mechanism. - Results Tight junction integrity was compromised in both human ICIs colitis and our WildR mouse model. We determined that this barrier dysfunction is driven by activation of the MLCK1-mediated leak pathway following ICI treatment. Using murine models, we identified tumour necrosis factor secreted by CD8+ and CD4+ T cells as an upstream regulator that induces colitis through this MLCK-dependent mechanism, as genetic deletion of MLCK preserved the tight junction structure and ameliorated the inflammation and ICIs colitis. Furthermore, a pharmacological screen identified the small molecule Epicatechin, which blocks MLCK1-FKBP8 interaction and inhibits the recruitment of MLCK1 to the perijunctional actomyosin ring and prevents the intestinal barrier loss. Finally, treatment with Epicatechin mitigated ICI-induced colitis without compromising the antitumour efficacy of the immunotherapy. - Conclusions These findings suggest that MLCK1-dependent tight junction regulation is essential for ICIs colitis, positioning barrier restoration as a potential therapeutic strategy.